Design and development of online survey system / Tan Fang Yen - Tan, Fang Yen (2005)
Doing survey is one of the unavoidable events. But the key point is how far a survey can be conducted in a moderately effective and efficient way? Doing survey online is advisable and since an idea of Online Survey System (OSS) is being advocated. OSS, or in other saying, a web based survey system, is being introduced in order to reduce or mitigate, even to complement the drawbacks of manual/ traditional methods. OSS is implementing able as long as the Internet access is available within the user's mean. Besides, the user is required to have at least one email account. With the event of OSS, the users can create and design their own interactive online survey. OSS provides a fast and wide distribution of survey form to a large geographical area through email. The related respondents just need to click on the attached URL in the invitation email. Then they will be directed to the survey area. Afterward the OSS will generate analysis report based on the responses collected. Users will be able to get the results in tabular and pictorial forms.